Developing an International Framework and Agenda for Agricultural Communications Research - David Doerfert; James Evans; Dwayne Cartmell; Tracy Irani (Journal of Applied Communications, 2007)
Timely, effective research is becoming a vital tool for communicators to use in the dynamic setting of the information age. Increasingly, it can support effective communications and decision-making related to agriculture. The authors report results of their recent efforts as members of a national project to envision a framework and agenda for agricultural communications research during the next 5 years. Noting the emergence and dynamics of the information age, they emphasize the centrality and resilience of agriculture. They observe how the agriculture-related sectors - food, fiber, natural resources, bio-based energy, nutrition and health, rural development, and others - tend to transform themselves and adapt over time and across societies. Similarly, the roles of communicators are adapting beyond that of the historical "town crier." Increasingly, communicators are helping people gather and share information, deliberate, sort through the mountains of information, select what they need, and make decisions. The authors identify 4 research priority areas and 18 key questions for research that communicators can use to address such challenges. They also suggest agricultural knowledge management as an integrative, international framework for strengthening this research agenda.